Mail Transfer During the First Reign of Prince Miloš - Milojević, Vesna O. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The mail transfer in Serbia can be tracked from Menzulana’s post stations, Tatarian courier service, and appointment of the chief supervisor to Constitution of postal administration which enabled a gradual transformation of this state institution into the system similar to current one. This transformation followed the Serbian authorities’ struggle for national independence which Prince Miloš Obrenović endeavoured to establish trying to improve a postal network at the same time, so that a postal network with suitable staff could satisfy the needs of all citizens of Serbia.